Description of Teacher Responses to the Implementation of Student Process Skills Portfolio Assessment - Harizon Harizon; Asrial Asrial; Haryanto Haryanto; M. Dwi Wiwik Ernawati; Dwi Agus Kurniawan; Feliza Paramitha Sinaga; Rizki Haryati (Integrated Science Education Journal, 2023)
Purpose of the study: This research aims to describe the response of science subject teachers to the assessment of students' process skills portfolios. Methodology: The research method used in this research is mixed, namely a combination of qualitative and quantitative methods. The research design chosen was a sequential explanatory design. This design was selected because quantitative research was carried out first and followed by qualitative methods. This design ensures that the quantitative data obtained is strengthened with qualitative data. Quantitative data analysis techniques are carried out using descriptive statistics. Meanwhile, qualitative data was analyzed based on Miles and Huberman's theory. The instrument used to collect quantitative data is a questionnaire sheet to measure teacher responses in portfolio assessment. Meanwhile, qualitative data was obtained from interviews and documentation studies on relevant problems. The population of this research is schools in Jambi Luar Kota District. The research sample is science subject teachers. The sampling technique used was cluster random sampling. Main Findings: The results obtained are the teacher's response in State Junior High School 1 Muaro Jambi superior to State Junior High School 1 Atap Pematang Jering. Novelty/Originality of this study: The urgency of this research is seen from the importance of assessment in learning activities, which is a tool for measuring student abilities and evaluating the education system. The background of this research is limited by the sample involved being only science subject teachers, and the population chosen is the Jambi Luar Kota sub-district.